2017 IEEE 26th International Symposium on Industrial Electronics (ISIE) 2017
DOI: 10.1109/isie.2017.8001375
|View full text |Cite
|
Sign up to set email alerts
|

Being a member of an energy community: Assessing the financial benefits for end-users and management authority

Abstract: -Since 2011, in the context of sustainable development, UK government has been encouraging individuals to work as groups, and now, more than 5,000 community led projects are sprouted across the country, since more than 50% of the UK citizens had expressed their interest to get involved with energy communities if they can potentially reduce their electricity cost. The aim of this study is to quantify the financial benefits for end-users and energy management authority when an energy community is settled up. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The model which was used in this study for the battery can be found in [13] and the power converter model in [14]. Briefly, the battery model used is an advanced R in model: a voltage source which varies with the battery SOC, in series with a resistance which depends (inverse proportional) on the battery capacity.…”
Section: Model Usedmentioning
confidence: 99%
“…The model which was used in this study for the battery can be found in [13] and the power converter model in [14]. Briefly, the battery model used is an advanced R in model: a voltage source which varies with the battery SOC, in series with a resistance which depends (inverse proportional) on the battery capacity.…”
Section: Model Usedmentioning
confidence: 99%
“…The design algorithms made use of already developed ESS models -the description of the models used (battery, power converter, overnight charging control algorithms etc. ), can be found in [26], and the energy management and power flow control applied in [27]. peak hours.…”
Section: B Inputs Processingmentioning
confidence: 99%
“…The battery model used in this paper was the one presented in [5]. The model is described by a detailed Rint electriccircuit, with a variable voltage source and an internal resistance, as shown in Fig.4.…”
Section: ) Battery Modelmentioning
confidence: 99%
“…There are four energy activities that the examined community gets involve to: generate energy (PV installations at specific community houses), reduce circulation of power (by controlling the energy flow), manage energy (balancing local supply and demand instantly) and purchase energy (collective trading among community members and grid) [5]. Energy communities can potentially unlock opportunities for their members by reducing energy bills, by decreasing carbon emissions and by promoting the local engagement, the energy security, the leadership and the control of the energy flow [3], [4], and [6].…”
Section: Introductionmentioning
confidence: 99%